KONTRA HEGEMONI MELALUI PERSPEKTIF VAN DIJK PADA FILM THE TRUE COST SEBAGAI REFLEKSI FAST FASHION INDUSTRIES - Wahjudi, Sugeng (Universitas Bunda Mulia, 2019)
ABSTRACTMedia functions as a tool to convey justice as a form of struggle. One of which is pictured through the documentary film The True Cost directed by Andrew Morgan and played by a lot of intellectual people one of which is Lucy Siegle as a journalist and environment columnist. This research is conducted with the purpose of understanding the contra hegemony actions towards the fast fashion industry which is portrayed in the documentary film The True Cost. This research is also conducted with the purpose to understand critically on what ideology is being offered by the actor and director of The True Cost documentary film against hegemony of the fast fashion industry. The author uses the critical paradigm which is used to find out the truth which actually happens behind the injustice and imbalance that exists. The author also uses the qualitative approach, which is the research to think inductively by using the Teun A Van Dijk Critical Discourse Analysis through stages of text, social cognition and social context. The subject of this research is the discourse of contra hegemony towards fast fashion, while the object is the documentary film The True Cost.Keywords: Gramsci, Contra Hegemony, Fast Fashion, Capitalism, The True CostÂ ABSTRAKMedia menjadi alat untuk menyampaikan keadilan sebagai bentuk perjuangan. Salah satunya tergambarkan dalam film dokumenter The True Cost yang disutradari oleh Andrew Morgan dan diperankan oleh banyak kaum intelektual salah satunya Lucy Siegle sebagai jurnalis dan kolumnis lingkungan. Penelitian ini dilakukan bertujuan untuk mengetahui tindakan kontra hegemoni atas industri fast fashion yang ditampilkan dalam film dokumenter The True Cost. Penelitian ini juga bertujuan untuk mengetahui secara kritis akan ideologi apa yang ditawarkan oleh aktor dan sutradara film dokumenter The True Cost dalam melawan hegemoni industri fast fashion. Peneliti menggunakan paradigma kritis yang digunakan untuk mencaritahu kebenaran yang sebenarnya terjadi di balik ketidakadilan atau ketidakseimbangan yang ada. Peneliti juga menggunakan pendekatan kualitatif, yaitu penelitian untuk berfikir induktif dengan menggunakan Analisis Wacana Kritis Teun A Van Dijk melalui tahap teks, kognisi sosial dan konteks sosial. Subjek dari penelitian ini adalah wacana kontra hegemoni terhadap fast fashion, sedangkan objeknya adalah film dokumenter The True Cost.Kata Kunci: Gramsci, Kontra Hegemoni, Fast Fashion, Kapitalisme, The True Cost